Modeling of processes of friction and wear in tribosystems in the conditions boundary lubrication. Part 2. The simulation results - Войтов, В.А.; Захарченко, М.Б. (Problems of Tribology, 2015)
A mathematical model for calculating the wear rate and friction coefficient tribosystems operating under boundary lubrication, which allows you to define resource and mechanical friction losses projected tribosystems without prior эксперимента was developed. The model takes into account the property of the material compatibility in tribosystem which received definition as Q-factor tribosystem. The results of modeling the wear rate and friction coefficient of various designs tribosystems with the assessment of the adequacy and modeling errors are shown.